A 5‐Year Retrospective Study on Replace Select Tapered Dental Implants. (2nd July 2013) - Pettersson, Pelle; Sennerby, Lars
Abstract Background Long‐term data regarding survival and crestal bone loss for Replace Select Tapered implants (Nobel Biocare AB, Gothenburg, Sweden) are lacking. Purpose The study aims to present the 5‐year outcomes from a retrospective analysis of Replace Select Tapered implants placed and restored in consecutive patients. Materials and Methods A total of 88 consecutive patients (32 male, 56 female, mean age 65 ± 12 years) treated by one clinician (PP) were clinically and radiographically evaluated during at least 5 years of function. A total of 271 dental implants (Replace Select Tapered, Nobel Biocare AB) with an oxidized surface (TiUnite, Nobel Biocare AB) had been placed in both jaws (228 in the maxilla, 43 in the mandible). The majority of implants were placed in healed sites (n = 244), while 27 implants were immediately placed in extraction sockets. The majority of implants (n = 262) healed for 3 to 4 months prior to loading, and nine implants were immediately loaded. A total of 121 implant‐supported restorations were delivered; 42 single tooth replacements, 61 fixed partial bridges, 14 fixed full bridges, and 4 fixed partial implant‐tooth connected bridges. The marginal bone level was measured in intraoral radiographs taken after surgery (baseline), and after 1, 2, 3, 4, and 5 years. Results Fifty‐one patients with 160 implants were followed throughout the study. One implant failed at healing abutment connection 4 months after insertion, resulting in a cumulative survival rate of 99.6%. The average crestal bone loss was 0.9 ± 1.6 mm after 1 year and 0.1 mm ± 2.4 after 5 years. There were 14.8% of measured implants that showed more than 2 mm and 5.2% more than 3 mm bone loss after 5 years, with no progression since the 1‐year examination. One patient (2.0%) treated with six implants presented with significant crestal bone loss and recurrent peri‐implant purulent infections at all implants. Conclusion The present retrospective 5‐year study showed high survival rate and steady crestal bone levels for Replace Select Tapered dental implants.